Political Activism in Canada: When Tibetans in Toronto Enter into Local Politics - Anne-Sophie Bentz (South Asia Multidisciplinary Academic Journal)
This article investigates the political mobilization of Tibetans in Toronto. I develop the hypothesis that Tibetans in Toronto who enter into local politics are already politicized, which facilitates the transition from activism within the Tibetan community to activism in Canadian society. To explore this transition from an inward- to an outward-looking type of mobilization, I draw on theoretical insights about the political integration of migrants developed by leading scholars in Social Movement Studies and Diaspora Studies. The careers of the two Tibetans who stood for office in Toronto in 2018, Bhutila Karpoche and Kalsang Dolma, as well as of Tibetan blogger and campaign manager Gelek Badheytsang, then serve to analyze the “strategic action fields” (Fligstein and McAdam 2012) or “arenas” (Jasper and Duyvendak 2015) invested by the Tibetans who choose to enter into local politics.